Does an accelerometer accurately measure steps taken under controlled conditions in adults with mild multiple sclerosis? - Motl, Robert W.; Snook, Erin M.; Agiovlasitis, Stamatis (Disability and health journal, 2011)
Accurate measurement is required by researchers and clinicians who are interested in the physical activity behavior of individuals with multiple sclerosis (MS). Advances in technology have resulted in an increased number of motion sensors such as pedometers and accelerometers that are worn on the body and that measure bodily movement. Accelerometers are becoming less expensive and more user-friendly, but there is limited evidence regarding the accuracy of measurement in persons with MS. The present study examined the accuracy of an ActiGraph accelerometer for measuring steps taken during controlled conditions in persons with MS compared with a sample of individuals without MS. The participants were 24 adults with mild MS and 24 adults without MS who undertook three 6-minute periods of walking at 54, 80, and 107 m·min −1 on a motor-driven treadmill. We measured steps taken through observation and an ActiGraph model 7164 accelerometer worn around the waist above the right hip. The accelerometer accurately measured steps during moderate (80 m·min −1) and fast (107 m·min −1) walking in both persons with MS and control subjects. There was a small degree of underestimation of step counts (≈4% error) for the accelerometer during slower walking (54 m·min −1) in both persons with MS and control subjects. Such findings support the accuracy of a waist worn ActiGraph accelerometer for the measurement of steps in persons with MS and control subjects.